2009
DOI: 10.1159/000209264
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Na,K-ATPase Increase and Potassium Dysregulation Accentuate the Risk of Postoperative Atrial Fibrillation

Abstract: Background: Postoperative atrial fibrillation is a common complication to cardiac surgery. Na,K-ATPase is of major importance for the resting membrane potential and action potential. The purpose of the present study was to evaluate the importance of Na,K-ATPase concentrations in human atrial biopsies and plasma potassium concentrations for the development of atrial fibrillation. Methods: Atrial myocardial biopsies were obtained from 67 patients undergoing open chest cardiac surgery. Na,K-ATPase was quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
1
7
0
1
Order By: Relevance
“…This data suggests that even brief episodes of ischemia-reperfusion during off-pump surgery may cause local injury currents in the atria, which may be significant because the atria are the most sensitive to high K + (Figure 5). In 2009, Tran and colleagues also reported a link between plasma K + during cardiac surgery and post-operative atrial fibrillation (Tran et al, 2009). Thus, hyperkalemia, whether imposed on the heart from depolarizing K + in surgical cardioplegia or from bouts of regional ischemia during beating heart surgery, may be linked functionally to membrane depolarization and an activated endothelium and inflammatory response, which collectively promote the generation of atrial (and ventricular) arrhythmias.…”
Section: Five Areas Of Concern With Hyperkalemic Cardioplegiamentioning
confidence: 99%
“…This data suggests that even brief episodes of ischemia-reperfusion during off-pump surgery may cause local injury currents in the atria, which may be significant because the atria are the most sensitive to high K + (Figure 5). In 2009, Tran and colleagues also reported a link between plasma K + during cardiac surgery and post-operative atrial fibrillation (Tran et al, 2009). Thus, hyperkalemia, whether imposed on the heart from depolarizing K + in surgical cardioplegia or from bouts of regional ischemia during beating heart surgery, may be linked functionally to membrane depolarization and an activated endothelium and inflammatory response, which collectively promote the generation of atrial (and ventricular) arrhythmias.…”
Section: Five Areas Of Concern With Hyperkalemic Cardioplegiamentioning
confidence: 99%
“…Within the normal range for serum K concentrations, this risk was increased three fold for patients with low serum K concentration compared to patients with high serum K concentration [3,4]. In addition, impaired K homeostasis has been found to be of importance for the development of atrial fibrillation [5]. Finally, it should be noted that hypokalemia has been reported to be insufficiently handled in 24% of hospitalized patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…It may be advisable to avoid hypokalemia when using b adrenoceptor agonists and to maintain pK in the upper normal range if at the risk of arrhythmia. development of atrial fibrillation [5]. Finally, it should be noted that hypokalemia has been reported to be insufficiently handled in 24% of hospitalized patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that elevated epinephrine arising from preoperative anxiety stimulated the b-2 adrenoceptor and the Na/K-ATPase that transports potassium into liver or skeletal muscle cell bodies and reduces extracellular and plasma potassium concentrations [11][12][13][16][17][18][19]. Previous studies reported that preinduction serum potassium concentrations were significantly lower than those measured in the outpatient department, a finding which was attributed to increased catecholamine due to preoperative anxiety, as determined by measurements of serum epinephrine levels [11,12].…”
Section: Discussionmentioning
confidence: 99%